Influencer Marketing as a Marketing Strategy - Ponirah, Ade (Journal of Economicate Studies, 2020)
This article discusses influencer marketing as a marketing strategy. The method used in this study is a method of literature sourced from books, research reports, journals, and websites. The findings of this article found that: (1) The rise of social media users became an opportunity for online marketing; (2) Influencer marketing is one of the most effective strategies used by companies to increase sales; (3) Influencers selected who already have personal branding and followers quite a lot; (4) Using this strategy will interest consumers and influence purchasing decisions.